Analysis of the Laws and Ethics of Contraception, Sterilization and Abortion with the Socio-Cultural and Religious Issues in Nigeria - Obalum, Dike Chijioke; Agwu, Sunday Kenechukwu (ABUAD Law Journal, 2023)
Modern science has developed through the centuries, particularly in the 21st century. These developments have constantly met the needs of humans in different aspects of life. The health care sector has not been left out in this rapid development. There has been significant development and improvements in reproduction by aiding families in reproduction and safe delivery. This paper adopted the doctrinal method of research and examined the flipside of healthcare development towards reproduction, which is the prevention through means such as contraceptives, sterilization and particularly abortion. The paper aimed at analyzing the law and ethics of contraception, sterilization and abortion and the relation of cultural and religious issues. In pursuit of this aim, the papers set out objectives such as clarification of the terms contraceptives, sterilization, and abortion, review of the laws and ethics of contraceptives and abortion around the world and analysis of the laws and ethics of contraceptives and abortion in Nigeria. The paper, among other things found that these developments have been met with different reactions from people in different regions of the world. The paper further found that these reactions have been mostly from cultural and religious perspectives. The development in this area of biological sciences has proven to aid better development in certain regions while others have not been met with such encouragement as people have been legally prohibited from using these medicinal instruments. The findings in this paper will be useful to both medical and non-medical practitioners. It will indeed be of immense benefit to the general society. The paper made recommendations for developing countries such as Nigeria on best practices to adapt.